Internationalisation and Cross-Border Mobility in Indian Higher Education - N.V. Varghese (International Journal of African Higher Education, 2020)
With the end of the Cold War political returns on foreign aid diminished. Many countries came to recognise trade as a more development-friendly modality than aid. Internationalisation of higher education also shifted from aid related cooperation agreements to market mediated cross-border trade arrangements within the framework of the General Agreement on Trade in Services (GATS). This article examines the changing face of internationalisation of higher education with a focus on the Indian experience. It argues that while internationalisation and cross-border mobility are mediated by market processes and economic rationality in most countries, the Indian government’s initiatives to internationalise Indian higher education are motivated by extending diplomatic relations to enable the country to play a more prominent role in global affairs.